Decarbonizing Rural Buildings and Rural Energy System China Building Energy and Emission Yearbook 2024 - Tsinghua University, Building Energy Research Center; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book focuses on China$1 (Bs building energy consumption and CO2 emissions, to discuss the status quo of China$1 (Bs building energy in four categories, their characteristics and technologies to improve energy efficiency and achieve zero-carbon emission. Carbon peaking and carbon neutrality targets have been one of the main motivations and goals for China$1 (Bs social and economic development. Building is one of the most important sectors to achieve energy saving and emission reduction. In particular, this book discusses the pathways to achieve the carbon neutrality target for China$1 (Bs rural buildings and rural energy system. This book analyzes the energy system transformation, technology perspectives to implement energy and carbon target in rural building sector. This book consists of large scale of survey data, monitoring data, and case studies. The discussion on technologies and policies is supported by a variety of evidences and continuous research for more than ten years. The information, data, and policy suggestions will be of interest to national and international audiences working in the fields of energy, climate change, engineering, and building science areas.s
Staging and Chronology of Archaeological Cultures in the Nenjiang River Basin -- Staging and Chronology of Archaeological Cultures in the Liaoxi Mountainous Region -- Staging and Chronology of Archaeological Cultures in the Liaoxi Plain -- Staging and Chronology of Archaeological Cultures in South Liaodong -- Staging and Chronology of Archaeological Cultures in North Liaodong -- Six Staging and Chronology of Archaeological Cultures in the West Songhua River Basin -- Staging and Chronology of Archaeological Cultures in the Tumen River Basin -- Northeast China during the Xia to Warring States Period: A Temporal and Spatial Framework of the Archaeological Cultures -- Pedigree Relations between Archaeological Cultures in the Northeast from Xia to Warring States Period.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Buildings -- Design and construction; Buildings -- Environmental engineering; Energy policy; Energy and state; Power resources; Building Construction and Design; Building Physics, HVAC; Energy Policy, Economics and Management; Natural Resource and Energy Economics